Über den Alltag hinaus : Festschrift für Thomas O. Höllmann zum 65. Geburtstag. - Selbitschka, Armin (Harrassowitz Verlag, 2018)
In 21 contributions, students and companions from Munich, Münster, Göttingen, Heidelberg, Cambridge and Oxford (GB), Los Angeles (CA), Tempe (AZ), Beijing and Shanghai honor the internationally renowned sinologist and now President of the Bavarian Academy of Sciences Thomas O. Höllmann on the occasion of his 65th birthday. Taking Höllmann's diverse research interests into account, the Festschrift brings together studies from the fields of archeology, history, art, philosophy and ethnology. They illuminate various aspects of daily life, especially in China, from ancient times to the present. This includes the inclusion of foreign technologies in bronze processing as well as the investigation of rituals and forms of living in early Chinese history, the reassessment of two fundamental inscription texts from the early imperial era and the modern reinterpretation of classic Confucian wedding celebrations. The studies of Chinese history are supplemented by contributions to urban life of the educated upper class in ancient India and to life with ruins in ancient Rome. In this way, this versatile volume offers not only sinologists, but also archaeological, historical, art-historical, philosophical and ethnologically interested readers numerous opportunities to discover new things.